2016
DOI: 10.1177/0022022116672488
|View full text |Cite
|
Sign up to set email alerts
|

Applying Multilevel Modeling to Understand Individual and Cross-Cultural Variations in Attitudes Toward Homosexual People Across 28 European Countries

Abstract: Individual and cross-cultural factors associated with attitudes toward homosexual people were examined in this study. Using cross-sectional data from the sixth biennial European Social Survey, which represents 36,959 individuals nested within 28 European countries, successive nested models were tested using multilevel modeling (MLM). Results found that attitudes varied cross-culturally as a function of people’s country of residence—this clustering effect was controlled for in all subsequent models. Individual-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 59 publications
3
28
0
1
Order By: Relevance
“…Poland is a conservative country (Donaldson et al 2017) oriented toward traditional values (Inglehart and Baker 2000), with a high position for the Catholic Church (Golebiowska 2017) and with one of the most restrictive laws related to…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Poland is a conservative country (Donaldson et al 2017) oriented toward traditional values (Inglehart and Baker 2000), with a high position for the Catholic Church (Golebiowska 2017) and with one of the most restrictive laws related to…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers pointed out that although values and attitudes toward family and work are still changing after the political transformation in Poland, gender roles seem to still be strongly aligned with traditional features (Siemieńska 2008). This statement found confirmation in the study of Donaldson et al (2017), who showed that social conservatism in Poland, defined as an adherence to traditional ideology, obtained a score of 4 of 5 (where 5 denotes the highest level of this country-level variable). Similarly, a study by Treas and Tai (2016) showed that Poland, like other post-socialist countries, is characterized by low gender egalitarianism.…”
Section: Gender Issues In a Polish Contextmentioning
confidence: 97%
See 3 more Smart Citations